Periorbital Dirofilariasis: A Rare Case from Western India - Shubha Nagpal; Varsha Kulkarni (Journal of Clinical and Diagnostic Research, 2016)
Dirofilariasis is a zoonotic disease caused commonly by Dirofilaria repens and Dirofilaria immitus. The definitive hosts are domestic dogs and cats. Human beings are accidental dead end hosts, and acquire infestation through mosquito bites. So far, very few cases have been reported from western India. We report a case of a 27-year-old male who presented with preseptal cellulitis right eye and a firm mass in the lower lid. Histopathological examination after surgical excision of the mass revealed a diagnosis of dirofilariasis. Although rare in Western India a diagnosis of dirofilariasis should be considered in cases of preseptal cellulitis associated with a periorbital mass.